Short bowel syndrome joint experience of a rare pathology. - Misa, Ricardo; Olano, E; Pellejero, M; Ferradas, Ana; Mira, Dora (Cirugía del Uruguay, 2002)
The Short Intestine Syndrome is the result of the reduction in extension of intestinal mucosa and leads to the malabsorption of nutrients and denutrition. This clínica! condition is inrequent, but in no way exceptional.